Structural modulation and assembling of metal halide perovskites for solar cells and light‐emitting diodes - Xixia Liu (Wiley, 2021)
Abstract Metal halide perovskites possess appealing optoelectronic properties and have been widely applied for solar energy harvesting and light emitting. Although perovskite solar cells (PeSCs) and perovskite light‐emitting diodes (PeLEDs) have been developed rapidly in recent years, there are still no universal rules for the selection of perovskites to achieve high‐performance optoelectronic devices. In this review, the working mechanisms of PeSCs and PeLEDs are first demonstrated with the discussion on the factors which determine the device performance. We then examine the optoelectronic properties of perovskites with structures modulated from 3D, 2D, 1D to 0D, and analyze the corresponding structure‐property relationships in terms of photo‐electric and electric‐photo conversion processes. Based on the unique optoelectronic properties of structurally modulated perovskites, we put forward the concept of structural assembling engineering that integrate the merits of different types of perovskites within one matrix and elaborate their excellent properties for applications of both PeSCs and PeLEDs. Finally, we discuss the potential challenges and provide our perspectives on the structural assembling engineering of perovskites for future optoelectronic applications.